Patients' Knowledge, Attitudes, and Behaviors Toward Family Doctors When They Attend A Private Primary Care Center - Alqarni , Abdullah Saeed; Alalyani, Abdullah Saad; Al Malki, Bader Abdulrahman; AlGhamdi, Muhannad Abdulqader; Algshanen, Mesale Ali Jaber; Hakeem, Moayad Abdulhameed; Asiry , Bushra Ali; Alotaibi , Saad Abdulrahman; Almutairi , Amjaad Mohammed; Aljohani , Afaf Mubarak (Journal of Ecohumanism, 2024)
Background: Healthcare systems often face imbalances, with tertiary care centers overburdened due to insufficient utilization of primary care. Family physicians, key players in holistic and cost-effective healthcare delivery, are underutilized due to limited public awareness. This study aimed to assess the knowledge, perceptions, attitudes, and practices of patients visiting a private primary care center regarding family physicians to support the promotion of family medicine as a vital specialty. Methods: This study was conducted at a primary care center. A pre-tested questionnaire collected data from 300 patients meeting inclusion criteria. The questionnaire evaluated socio-demographic information, knowledge, perceptions, attitudes, and practices concerning family physicians. Responses were analyzed using descriptive statistics and SPSS version 19.0. A 5-point Likert scale was employed, with results condensed into three categories for simplicity. Results: Participants demonstrated high awareness (96.7%) of the role of family physicians and expressed strong confidence in their abilities to provide holistic and cost-efficient care. Positive attributes such as attentive listening, professionalism, and patient involvement in decision-making were acknowledged by over 95% of respondents. While 88% identified family physicians as their preferred initial healthcare contact, actual practice patterns revealed preferences for specialists in areas like pediatric care (66.2%), obstetrics (81.6%), and diabetes management (52%). Consistent consultations improved patient familiarity and rapport with family physicians. Conclusion: Despite favorable knowledge and attitudes, many patients opted for specialists over family physicians for specific health concerns. Further initiatives to enhance public awareness, address perception gaps, and expand the scope of family medicine are essential to strengthen its role in integrated healthcare systems.